2007
DOI: 10.4161/cbt.6.1.3551
|View full text |Cite
|
Sign up to set email alerts
|

Profile of Ets gene expression in human breast carcinoma

Abstract: Background: Ets genes encode a family of transcription factors that play key roles in cell proliferation, differentiation and apoptosis. Fusions of Ets genes with other targets have been described in Ewing's sarcoma, chronic myelomonocytic leukemia and more recently prostate carcinoma. Ets expression in breast carcinoma has not been comprehensively studied, and is the focus of this study.Methods: RT-Q-PCR was used to determine the expression of Ets genes in a panel of ten common breast cancer cell lines, two i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
57
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(64 citation statements)
references
References 34 publications
(37 reference statements)
6
57
1
Order By: Relevance
“…Alternatively, since the anti-PDEF antibodies used in two of the three previous studies (19,20) were generated against the full-length PDEF protein, they carried the potential for crossreaction with other Ets factors in the immunohistochemical assay. The latter potential stems from: i) the high degree of sequence homology approaching 45 to 55% amino acid sequence identity in the DNA binding domain between PDEF and other Ets factors (11); and ii) the large number of Ets factors that are expressed in normal mammary gland, and several at much higher levels than Pse or PDEF (17,22). The third study (21) used antibody raised against the same N-terminal segment of PDEF as used in this study, however, the specificity of the immunohistochemical assay for PDEF was not demonstrated in that study.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, since the anti-PDEF antibodies used in two of the three previous studies (19,20) were generated against the full-length PDEF protein, they carried the potential for crossreaction with other Ets factors in the immunohistochemical assay. The latter potential stems from: i) the high degree of sequence homology approaching 45 to 55% amino acid sequence identity in the DNA binding domain between PDEF and other Ets factors (11); and ii) the large number of Ets factors that are expressed in normal mammary gland, and several at much higher levels than Pse or PDEF (17,22). The third study (21) used antibody raised against the same N-terminal segment of PDEF as used in this study, however, the specificity of the immunohistochemical assay for PDEF was not demonstrated in that study.…”
Section: Discussionmentioning
confidence: 99%
“…20 EHF has been shown to be differentially regulated in prostate, serous ovarian, and breast carcinomas. [19][20][21] S100A8 is a calciumbinding protein that was also upregulated in our study comparing squamous cell carcinoma to pseudoepitheliomatous hyperplasia and squamous cell carcinoma to normal skin. 8,9 It is involved in the regulation of various cellular processes, and its role in tumorigenesis was previously discussed.…”
Section: Discussionmentioning
confidence: 99%
“…55 Moreover, higher levels of ESE-1 mRNA and protein expression were detected in breast cancer cells than in normal breast epithelial cells, and an overexpression of ESE-1 has been observed in primary breast tumor specimens as compared to normal mammary tissues. 56 ESE-1 expression is also upregulated in a subset of breast tumors and breast cancer-derived cell lines that express high levels of the Her2/Neu proto-oncogene, which is also known as erythroblastic leukemia viral oncogene homolog 2 (ErbB-2). 54 Transient reporter assays using the ESE-1 promoter have shown that ESE-1 transcription is regulated by ErbB-2 receptor signaling in epithelial breast cancer cells, where expression of ErbB-2 upregulates ESE-1 promoter activity, while inhibition of ErbB-2 or its downstream signaling pathways decrease both ESE-1 promoter activity and endogenous ESE-1 protein levels.…”
Section: Ese-1 In Mammary Gland Development and Breast Cancermentioning
confidence: 99%